The Process of Dissimilation in English and Arabic: A Comparative Study - Faiq, Aseel Muhammad; Burhanuddin, Israa (Sulaimani Journal for Humanities, 2025)
Unlike the process of assimilation, which is a phonological process in which two sounds that are different become more alike, dissimilation is a process in which sounds that are alike become different.The present paper is concerned with showing dissimilation process in both English and Arabic languages. It seeks to investigate the main causes behind this process beside its main classifications and whether these causes and classifications are found in the two languages under study. The comparative analysis findings show that both languages share similar incentives and classifications and this, in turn, renders the process as being universal, sporadic and quantal (non-gradual). Moreover, it has been found that dissimilation is not only achieved by differentiating sounds, other processes may help to dissimilate elements and to make sounds more dissimilar and distinct.